Modulation of the human hair follicle pigmentary unit by corticotropin-releasing hormone and urocortin peptides - Kauser, Sobia (2006)
Human skin is a local source of corticotropin-releasing hormone (CRH) and expresses CRH and CRH receptors (CRH-R) at mRNA and protein levels. Epidermal melanocytes respond to CRH by induction of cAMP with up-regulation of pro-opiomelanocortin gene expression and subsequent production of adrenocorticotropin hormone. However, the role of CRH/CRH-R in melanocyte biology is complicated by the significant heterogeneity of cutaneous melanocyte subpopulations, from continuously active and UV-responsive melanocytes in epidermis to UV nonresponsive, hair growth cycle-coupled melanogenesis in hair follicles. In the present study we report that normal human scalp hair follicle melanocytes express CRH at the mRNA level. Furthermore, CRH, urocortin and CRH-R 1 and 2 were differentially expressed in follicular melanocytes, fibroblasts, and keratinocytes depending on anatomic location and differentiation status in situ and in vitro. Stimulation of follicular melanocytes with CRH and CRH peptides, modified for selectivity for CRH-R1 and/or CRH-R2, variably induced cell melanogenesis, dendricity, and proliferation. CRH-peptides also stimulated the expression and activity of Tyrosinase, and expression of Tyrosinase-related protein-1 and-2. However, a modified urocortin peptide highly selective for CRH-R2 down-regulated melanocyte differentiation phenotype. This study indicates that CRH peptides can differentially influence hair follicle melanocyte behavior not only via CRH-R1 signaling but also by complex cross-talk between CRH-R1 and CRH-R2.—Kauser, S., Slominski, A., Wei, E. T., Tobin, D. J. Modulation of the human hair follicle pigmentary unit by corticotropin-releasing hormone and urocortin peptides.